How Does a Building Company Perform in the CE? Analysis Taking into Account Organizational Levels and LCA Stages - Pedro NUNEZ-CACHO; Jaroslaw GORECKI; Juan M. MAQUEIRA-MARÍN (Communications of International Proceedings, 2020)
Society in general and the business world in particular start to behave sustainably. Therefore, we pay more and more attention to the principles of the Circular Economy (CE). The construction industry is no stranger to the problem and its companies are transitioning to this more sustainable production model. Society demands information about this transition, and it is not easy to establish when and with what degree of intensity a company implements the Circular Economy model. To provide a real and effective measurement system, we have designed a dashboard with the main KPIs of the construction industry, related to the CE. To do this, a review of the literature and analysis of the sustainability reports of the companies is first developed. Once the indicators are defined, they are classified into two levels, one based on the Life Cycle Analysis and the other based on the organization's level analysis. After that, a simulation is performed using the Monte Carlo technique. After multiple iterations, this method establishes the most likely KPI values as a result, which will be the limits used in the scorecard, establishing 23 critical indicators.
Keywords: Circular Economy; Construction Industry; Key Performance Indicators; Circular Economy Index; Dashboards.